Optimizing Injection Techniques for Avian Embryos: A Practical Model for Experimental Embryology - Nurin Nadzifatil Fitriyah; Suryani Suryani; Din Fitri Rochmawati; Ahmad Nafi Ulumi; Abd El Rahman Irwan Maulana; Putri Shavina Shaqynia Nasution; Fa’iqotur Rokhmah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Background:Avian embryos such as chickens and ducks offer an ethical and practical model to study early development and test experimental procedures. However, differences in in-ovo injection techniques can affect embryo survival and the consistency of results. This study aimed to find the most effective injection method to improve the success and reproducibility of avian embryo research. Methods: A total of 60 fertilized eggs (30 chicken and 30 duck eggs) were used. They were randomly assigned into six groups: control, horizontal injection, and vertical injection (10 eggs per group for each species). Each treated egg received 0.25 mL of sterile 0.9% saline through a fine 27G syringe and was incubated at 37±0.5°C with 55–60% humidity for five days. Embryo growth was evaluated daily based on the formation of blood vessels, which can be seen by examining the eggs, and differences in egg weight. After the fifth day, the eggs are broken open and the embryos are observed by body length, morphology formation. Results: Vertical injection through the pointed end of the egg resulted in the highest normal development rates (70% in chickens and 80% in ducks). In contrast, horizontal injection caused almost complete growth failure, while control embryos developed normally. Statistical analysis showed a significant effect of injection orientation on embryo survival (p < 0.01). Conclusion: Injecting vertically through the pointed end of the egg is a reliable and low risk method for manipulating avian embryos. This optimized approach ensures better embryo survival and can be applied in future studies involving developmental biology, toxicology testing, stem cell research, and gene editing experiments.